A propagação da crença escolar ou o "contágio da convicção": Os ritos de instituição no romance O Ateneu - Tiago Ribeiro Santos; Rita de Cássia Marchi (Universidade do Minho, 2013)
This article, in the interface of sociology of education with history of education, presents an analysis of the rites of institution described in the novel O Ateneu, authored by the Brazilian writer Raul Pompeia and originally published in 1888. The novel portrays the daily life of a wealthy school of the time. The rites of institution in Ateneu school act to produce - reproducing - the belief in school life, establishing differences among the targeted individuals. In this sense, ritual acts to convince the school agents of supporting and taking part in various activities of the school, collectively orchestrating the different interests, dispositions and modes of conduct.